Quelle reconnaissance des vulnérabilités au travail ? - Dominique Lhuilier (Perspectives Interdisciplinaires sur le Travail et la Santé)
The notion of vulnerability, which is increasingly present in the work world, is associated with demeaning attributes. The categorization and treatment of those who, individually or collectively, are labelled “vulnerable” contribute to the creation of a two-tier representation of the work world. The shift away from ontological vulnerability to a psychological projection and division process fosters a disincarnated and idealized conception of the self-reliant person. Nonetheless, disease and illness contribute to the deconstruction of this illusion. Sick people at work reveal how poorly adjusted contemporary work standards can be, anchored as they are in the denial of the fundamental corporal and temporal nature of our being. The political impact of work vulnerability and the social obligations that it implies are highlighted here : by acknowledging them, we humanize work.